DINAMIKA KERJASAMA PERDAGANGAN EKSPOR BERAS VIETNAM KE TIONGKOK DALAM ISU KONFLIK LAUT CINA SELATAN TAHUN 2011-2015 - Rizka Aprilini; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research will examine the dynamics of trade cooperation of Vietnamese rice exports to China in the South China Sea conflict issues that have influenced the relations between the two countries.The sources of data used in this research are books, journals, working papers, valid news from websites and newspaper, to describe the process by analyzing the phenomenon based on existing data.. To analyze the research question, the writer uses a perspective, specifically the perspective liberalism, use a Teori of The International Political EconomyThe relationship between Vietnam with China (China) is known to have a history that is long and winding. The success of the cooperation in the field of export of raw materials such as rubber, steel and vegetables is the largest and most rice, does not necessarily make relations between the two countries is free from conflict. Although Vietnam and China (China) adopts the same ideology, the ideology of communism, but often there are differences in political decisions. The highlight is a rift between the two countries occurred on 17 February 1979, where the Chinese do military invasion into the territory of Vietnam.Keyword: South China Sea, Dynamics of export Rice Trade Cooperation Between Vietnam And China Amid Conflict Issues South China Sea